A comparison method for calculating ground shaking - case study: Yogyakarta earthquake 2006 - A. S., Bawono; Mohamad Idris, Ali; F., Ma'arif (IOP Publishing Ltd., 2019)
This paper presents a comparison method for calculating ground shaking in Yogyakarta, especially in Sedayu Permai Housing, Bantul District. The study was based on Hazard US (HAZUS) with Ground Motion Prediction Equations. The suitable using the latest attenuation equation from [1] for the BC class site rock and global source subduction use. Therefore, is needed necessary from an experts' judgment to evaluate because different mechanism of earthquake for Indonesian seismic hazard.